Creativity in Dance: Conceptions, Methods and Choreographic Composition Processes in Dance Teaching - Marques, Ana Silva (2013)
Thinking about dance training, either in its generic artistic approach (Artistic Education), the doing, the creating, the learning, the appreciating or on its vocational artistic approach (Vocational Studies) where the aim are advanced studies leading towards future dance professionals (Interpreters and choreographers), we have to look into themes such as Creativity in Dance from different points of view. Considering that in these different points of view, we can aim for the intentional creation of artistic objects it´s essential to articulate around themes as: body awareness, movement, methods and choreographiccomposition processes and their articulation with the present artistic practice. On this article we cross distinct investigation lines which are developed in Doctoral Programmes, the objective being - to relate themes considered fundamental in Dance training which contribution will allow for the improvement of our own pedagogical intervention proposals.